1996
DOI: 10.1007/bf00045909
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of parsley through axillary shoot proliferation

Abstract: A micropropagation protocol of parsley, Petroselinum crispum (Mill.) Nyman (curled type) has been developed. Surface-sterilized axillary buds cultured on Murashige and Skoog medium supplemented with benzyladenine, kinetin, or thidiazuron developed axillary shoots (rosettes). Kinetin resulted in only a low proliferation rate. The concentrations of thidiazuron or benzyladenine that were optimal for shoot proliferation, resulted in shoots with a low capability to root. During the rooting treatment, these shoots s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…1). Favorable effects of these growth regulator combinations on shoot proliferation response has also been reported in Foeniculum vulgare (Du Manoir et al, 1985), Petroselinum crispum (Vandemoortele et al, 1996), Cicer arietinum (Barna and Wakhlu, 1995), Hedeoma multiflorum (Koroch et al, 1997) and lsoplexis canariensis (Arrebola et al, 1997). The regenerated shoots were healthy and attained a height of 4.31 cm within 4 wk.…”
Section: Resultsmentioning
confidence: 84%
“…1). Favorable effects of these growth regulator combinations on shoot proliferation response has also been reported in Foeniculum vulgare (Du Manoir et al, 1985), Petroselinum crispum (Vandemoortele et al, 1996), Cicer arietinum (Barna and Wakhlu, 1995), Hedeoma multiflorum (Koroch et al, 1997) and lsoplexis canariensis (Arrebola et al, 1997). The regenerated shoots were healthy and attained a height of 4.31 cm within 4 wk.…”
Section: Resultsmentioning
confidence: 84%
“…Two weeks after the transfer of embryos on hormonefree ½ MS culture medium, seedlings developed in vitro. It was previously reported that low concentration of an auxin in combination with a cytokinin positively modifies the shoot induction frequency and their growth (Yuan et al 1994, Vandemoortele et al 1996, Singh and Sehgal 1999, Çöçü et al 2004. 1B), shoots were used in experiments to evaluate the effect of cytokinins on multiple shoot formation from nodal explants.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%
“…- (Gopi & Ponmurugan, 2006). - (Vandermoortele, Billard, Boucaud, & Gaspar, 1996). - (Abbasi, Khan, Mahmood, Mushtaq, Chaudhary, & Khan, 2010).…”
Section: Rich (Eşek Hıyarı) -Doku Kültürümentioning
confidence: 99%